1999
DOI: 10.1128/iai.67.11.5979-5984.1999
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antibody Responses of Elderly Adults to All 23 Capsular Polysaccharides after Pneumococcal Vaccination

Abstract: The 23-valent pneumococcal polysaccharide vaccine was formulated to prevent invasive infection in the elderly and other high-risk populations from the most prevalent Streptococcus pneumoniae serotypes. However, the immunogenicity of all 23 vaccine polysaccharides has not been fully characterized in elderly adults. We previously reported that whereas the majority of elderly subjects had vigorous immune responses to selected pneumococcal vaccine polysaccharides, a subset of elderly individuals responded to fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 33 publications
4
18
0
2
Order By: Relevance
“…The analysis was performed at the Johns Hopkins University School of Medicine Reference Laboratory for Dermatology, Allergy and Clinical Immunology (Baltimore, MD) (good laboratory practice certified). The antibody serotypes for analysis were chosen based on the most frequently found serotypes associated with invasive pneumococcal infections in older individuals 14,30 . Sera preadsorbed with non‐type‐specific cell wall or C‐polysaccharide (Wyeth‐Lederle Vaccines) were added to polystyrene microtiter plate wells that had been previously coated with type‐specific pneumococcal polysaccharide.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was performed at the Johns Hopkins University School of Medicine Reference Laboratory for Dermatology, Allergy and Clinical Immunology (Baltimore, MD) (good laboratory practice certified). The antibody serotypes for analysis were chosen based on the most frequently found serotypes associated with invasive pneumococcal infections in older individuals 14,30 . Sera preadsorbed with non‐type‐specific cell wall or C‐polysaccharide (Wyeth‐Lederle Vaccines) were added to polystyrene microtiter plate wells that had been previously coated with type‐specific pneumococcal polysaccharide.…”
Section: Methodsmentioning
confidence: 99%
“…Two other studies have shown serotype 3 to be associated with excess mortality, 31,32 and in the polysaccharide vaccine, serotype 3 has been shown to have relatively poor immunogenicity for patients aged 65 years or older with chronic conditions. 25,33 Therefore, an expanded valent conju-gate vaccine that included serotype 3 may be of additional benefit to older adults if it could reduce transmission of this serotype.…”
Section: Mortalitymentioning
confidence: 99%
“…However, a protective titer of 0.35 lg/mL has been estimated through pooled analysis of vaccine efficacy studies with invasive disease endpoints and is discussed in the WHO technical report (15). Additionally, studies of pneumococcal vaccination in the elderly have shown a twofold response to be significant (17). Therefore, we chose a conservative and strict measure of response as a twofold rise in titer and an absolute titer greater than 0.35 lg/mL.…”
Section: Kumar Et Almentioning
confidence: 99%